Effects of Citric Acid on the Performance and the Utilization of Phosphorous and Crude Protein in Broiler Chickens Fed on Rice By-Products Based Diets - Atapattu, N.S.B.M.; Nelligaswatta, C.J. (International Journal of Poultry Science, 2005)
An experiment was conducted to study the effects of two levels of citric acid (CA) on the performance and the utilization of phosphorous and crude protein in broiler chickens fed on rice by-products based diets. Growth performance and feed conversion ratio (FCR) were not significantly affected by the inclusion of citric acid. pH of the contents of the crop was 5.1, 4.8 and 4 in control, 1% citric and 2% citric diets fed birds, respectively. Though not significant, 2% dietary citric acid increased the feed intake and thus resulted in poor FCR. Toe ash percentage was significantly (p< 0.05) increased by 2% citric acid. Though not significant, mineral retention was also improved by 2% dietary citric acid. Orthogonal contrast between control and citric acid given diets showed that dietary citric acid increased the digestibility of crud protein and crud fibre and dressing percentage. It is hypothesized that citric acid serves as proton donor for phytic acid and thus prevents the formation of insoluble complexes. Being an organic acid, citric acid may weaken the structure of CF thus making CP and phytate associated with them more susceptible for enzymatic digestion.